Identification of detectable area by applying inverse problem / Touil Dalal Radia … [et al.] - Dalal Radia, Touil; Ahmed Chaouki, Lahrech; Helifa, Bachir; Ibn Khaldoun, Lefkaier (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This work introduces the notion of the GMR sensor's effective area (EA) after being calculated and optimized using the inverse problem (Particle Swarm Optimization method). The operation of the differential GMR sensor is validated using a 3D Finite Element Model based on the (A, V–A) formulation and experimental measurements. The prototype of the differential GMR sensor is developed and tested.